2013
DOI: 10.1002/pbc.24907
|View full text |Cite|
|
Sign up to set email alerts
|

Pain management at home in children with cancer: A daily diary study

Abstract: A significant proportion of children receiving outpatient treatment for cancer were rated as experiencing chronic pain and pain was not optimally managed in the home setting. Further understanding and addressing barriers to children's cancer pain management in the home setting will aid in alleviating unnecessary pain in this vulnerable patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 36 publications
4
77
1
8
Order By: Relevance
“…Although parents and children who suffer from cancer report that pain is a significant concern, pain assessment throughout cancer treatment is not performed systematically [3,10–12] and without accurate data, physicians are unable to intervene appropriately. Additional barriers to treatment of pain in children with cancer include misunderstanding of use of analgesia in children (i.e., fears of addiction) and lack of understanding of pain expression in children [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although parents and children who suffer from cancer report that pain is a significant concern, pain assessment throughout cancer treatment is not performed systematically [3,10–12] and without accurate data, physicians are unable to intervene appropriately. Additional barriers to treatment of pain in children with cancer include misunderstanding of use of analgesia in children (i.e., fears of addiction) and lack of understanding of pain expression in children [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Additional barriers to treatment of pain in children with cancer include misunderstanding of use of analgesia in children (i.e., fears of addiction) and lack of understanding of pain expression in children [10,12,13]. This is particularly relevant to management of symptoms in the home setting by parents, who have been shown to significantly under treat children’s pain [3,14].…”
Section: Introductionmentioning
confidence: 99%
“…Parents have identified pain as the “most problematic” symptom children experience during cancer treatment and children have described pain as the most distressing and frightening aspect of their cancer experience . Unfortunately, evidence suggests that cancer pain and symptoms are seriously undertreated in most children, particularly in the home setting . Pain is not just an issue at diagnosis and during treatment for cancer.…”
Section: Problem 2: Pain In Children With Cancermentioning
confidence: 99%
“…11 However, it was observed that even small children with limited language resources were able to demonstrate, through the DTP sessions, how they perceive the routine which they experience.…”
Section: Immersing Oneself In the World Of The Disease And The Oncolomentioning
confidence: 99%